Свойства и пористая структура модифицированных отходов винодельческой промышленности [Articol] - Зеленцов, Вячеслав; Дацко, Татьяна; Ковалёв, Виктор (My University, 2005)
Two methods of modification of benthonite used in vine clarification have been applied: introduction of Na2S in report 1:10 into benthonite paste followed by pyrolysis at 450oC; electrotreatment of slime suspension in electrochemical cell (in anodic camera and in diaphragmless electrolizer). By means of thermogravimetric analysis some thermal effects attributed to different processes have been observed: removing of water (dehydratation), phase transformations, oxidation of organic compounds, crystallization and destruction of benthonite structure. Adsorption-structural characteristics of initial and modified samples of benthonite slimes have been examined and the mechanism of their change under thermo- and electrotreatment has been discussed.